PENGARUH KOMPOSISI MEDIA TANAH SUB SOIL DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN PINANG BETARA DI PEMBIBITAN - Suyetno, Suyetno; Asfaruddin, Asfaruddin; Aryani, Farida; Mulatsih, Sri (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
This study aims to determine the effect of various compositions of subsoil media and manure on the growth of Betara betel nut seedlings in nurseries. The experiment was carried out from January to May 2022 at the Ketahun BPDAS Nursery Post, Jalan Jati No. 39 Sawah Lebar Village, Ratu Agung District, Bengkulu City. The experiment used a randomized block design (RBD) consisting of five (5) treatments, namely Media Composition (M) with 5 replications. Each treatment consisted of 10 seeds a total of 250 seeds. The treatment for the composition of the Media (M) is as follows: M1: 100% Sub Soil; M2: Sub soil + Cow manure (3:1); M3: Sub soil + Cow Manure (2:1); M4: Subsoil + Cow Manure(1:1); and M5: 100% Top Soil. Observational data were analyzed by analysis of variance at the 5% confidence level, if it had a significant or very significant effect it was tested further with Duncan's Multiple Range test (DMRT) at a 5% confidence level. The results of the study concluded: (1) The treatment of media composition had no significant effect on plant height from 2 WAP to 8 WAP, number of leaves, root length, number of roots, root wet weight, root dry weight, and areca seedling wet weight, but had a significant and very significant effect significantly to plant height from 10 to 16 WAP, crown wet weight, and crown dry weight; (2) The best media composition for Betara's areca nurseries is the composition of subsoil mixed with cow manure in a ratio of 1: 1.